Robot Application for Hepatopancreatic Disorders, Gastroesophageal Reflux Disease, and Achalasia. Issue 3 (March 2022) - Rosemurgy, Alexander; Bourdeau, Timothy; Luberice, Kenneth; Sucandy, Iswanto; Ross, Sharona
Introduction: We undertook this study to describe the number and variety of robotic operations undertaken for hepatopancreatic and esophageal disorders. Methods: Data from 2015 through March of 2018 were analyzed for da Vinci™ robot application for hepatopancreatic disorders, gastroesophageal reflux disease (GERD), and achalasia. Results: From 2015 through 2017, robotic hepatopancreatic operations increased 49%, robotic hepatic operations increased 107%, and robotic pancreatic operations increased 26%. Quarter after quarter, robotic application increased for hepatopancreatic operations, hepatic operations, and pancreatic operations ( P < .001 for each) with acceleration over the most recent months. The application of the Xi robot platform increased from 12% of robotic hepatopancreatic operations in 2015-71% in 2018 (1075% increase in numbers). From 2015 through 2017, robotic fundoplications and myotomies increased by 55%, robotic fundoplications increased by 59%, and robotic Heller myotomies increased by 211%. Quarter after quarter, robotic application increased for fundoplications and Heller myotomies ( P < .001 for each) with acceleration over the most recent months. The application of the Xi robot platform increased from 13% of these robotic operations in 2015-64% in 2018 (935% increase in numbers). Less than 10% of hepatopancreatic operations, fundoplications, and myotomies are undertaken robotically. Conclusions: There has been an accelerating increase in the number of robotic operations for hepatopancreatic disorders, GERD, and achalasia over the past 3 ¼ years. Application of the Xi robot has dramatically increased, both absolutely and relatively. Still only a small proportion of operations for hepatopancreatic disorders, GERD, and achalasia use the robotic platform; this is changing fast.